Pluralism in Architecture - wahda shuker Al-Hangaweh (Iraqi Journal of Architecture and Planning, 2009)
whenÂ studying the concepts that form arclLitecture through analyzing itsresults along the time, the tension of intellect betwr:en the spiritual and intellectualaspects arises.The human civilizations through the history was always attempting to alienbetween the spiritual and metaphysical research , and the pure scientific researchconsidering the first as studying the mysterious pheno nena , while science deals withwhat is researchable subject to analysis which provides a concrete base for discussion, as it offers clear facts that coutd be experimente,l and tested , because sciencedemands from human beings to deal with the universe and the facts of life and deathrationally , whereas life proves everyday that not all tlLe genuine are realistic , and theinterpretation stays the flame structure through whi ch we look at facts of life in theprocess of searching for the variable in the invariable , and for all invariable in thevariables .The research includes an attempt to clarify the concept ofmonism andpluralism in the human intellect and the concept ol pluralism in the architecturalwork.The research has reached to explain the con,:ept ofpluralism in architecturethrough the changing of the intellectual concepts in p ost modern architecture againstthe concept of monism that modem architecture aC opted and their influence uponcreativity in architectural work.